2022
DOI: 10.1111/os.13408
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates the Progression of Osteoarthritis in Rats by Inhibiting Inflammation and Related Oxidative Stress on the Surface of Knee Cartilage

Abstract: Objective To investigate the correlation between melatonin and osteoarthritis (OA) in rats. To explore the relevant mechanisms in the occurrence and development of osteoarthritis in rats, and to further understand the disease of osteoarthritis. Methods Forty healthy 6‐month‐old male SD rats were randomly divided into two groups: sham and drug intervention groups. Pre‐OA modeling, enzyme‐linked immunosorbent assay was employed to detect the levels of IL‐1β, IL‐6, COX‐2, and melatonin in the serum of the rats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…IL-6 is closely related to cartilage matrix degeneration and synovial in ammation in OA development; through receptor binding, it can promote the formation of osteoclasts, and serum IL-6 level is positively correlated with the degree of cartilage damage. Studies have shown that IL-6 messenger RNA (mRNA) expression in synovial cells of patients with early knee OA is increased, which is consistent with the results of this study [12]. JUN is composed of c-Fos, c-Jun and other factors and can regulate the release of in ammatory substances, such as IL-8 and TNF, through the MAPK and PI3K/Akt signalling pathways, thus aggravating cartilage degeneration [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…IL-6 is closely related to cartilage matrix degeneration and synovial in ammation in OA development; through receptor binding, it can promote the formation of osteoclasts, and serum IL-6 level is positively correlated with the degree of cartilage damage. Studies have shown that IL-6 messenger RNA (mRNA) expression in synovial cells of patients with early knee OA is increased, which is consistent with the results of this study [12]. JUN is composed of c-Fos, c-Jun and other factors and can regulate the release of in ammatory substances, such as IL-8 and TNF, through the MAPK and PI3K/Akt signalling pathways, thus aggravating cartilage degeneration [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, MT preserves the proliferation and differentiation properties of BMSCs, enhancing their therapeutic effect. 64 In our previous study, we found that MT increased the expression of circRNA3503 and isolated circRNA3503-loaded sEV, which alleviated apoptosis and maintained the balance between synthesis and degradation of ECM. 30 Herein, we obtained sleep-related sEV by combining MT with sEV, and demonstrated that they simulate endogenous tissue repair mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…MT may inhibit inflammation and oxidative stress in cartilage to retard osteoarthritis progression and stimulate cartilage regeneration. In addition, MT preserves the proliferation and differentiation properties of BMSCs, enhancing their therapeutic effect 64 . In our previous study, we found that MT increased the expression of circRNA3503 and isolated circRNA3503‐loaded sEV, which alleviated apoptosis and maintained the balance between synthesis and degradation of ECM 30 .…”
Section: Discussionmentioning
confidence: 92%
“…Study has revealed that CBD can stimulate matrix synthesis by restoring glycosaminoglycan synthesis [46] . Histological examination using Mankin scoring showed that intra‐articular injection of LPS in rat knee joints induced cartilage structural changes, matrix degradation, and chondrocyte disorganization [47,48] . What's more, MMP‐13, a key enzyme of cartilage matrix degradation in osteoarthritis, expression was also inhibited.…”
Section: Discussionmentioning
confidence: 99%